Maturation of the Autonomic Nervous System in Premature Infants: Estimating Development Based on Heart-Rate Variability Analysis - Lavanga, Mario; Heremans, Elisabeth; Moeyersons, Jonathan; Bollen, Bieke; Jansen, Katrien; Ortibus, Els; Naulaers, Gunnar; Van Huffel, Sabine; Caicedo, Alexander (Frontiers in Physiology, 2021)
This study aims at investigating the development of premature infants' autonomic nervous system (ANS) based on a quantitative analysis of the heart-rate variability (HRV) with a variety of novel features. Additionally, the role of heart-rate drops, known as bradycardias, has been studied in relationship to both clinical and novel sympathovagal indices. ECG data were measured for at least 3 hours in 25 preterm infants (gestational age <= 32 weeks) for a total number of 74 recordings. The postmenstrual age (PMA) of each patient was estimated from the RR interval time-series by means of multivariate linear-mixed effects regression. The tachograms were segmented based on bradycardias in periods after, between and during bradycardias. For each of those epochs, a set of temporal, spectral and fractal indices were included in the regression model. The best performing model has R^2 = 0.75 and mean absolute error MAE = 1.56 weeks. Three main novelties can be reported. First, the obtained maturation models based on HRV have comparable performance to other development models. Second, the selected features for age estimation show a predominance of power and fractal features in the very-low and low frequency bands in explaining the infants' sympathovagal development from 27 PMA weeks until 40 PMA weeks. Third, bradycardias might disrupt the relationship between common temporal indices of the tachogram and the age of the infant and the interpretation of sympathovagal indices. This approach might provide a novel overview of postnatal autonomic maturation and an alternative development index to other electrophysiological data analysis.